Knotted reactors and their role in flow-injection on-line preconcentration systems coupled to atomic spectrometry-based detectors - Cerutti, Estela Soledad (2005)
The progress in flow-injection (FI) on-line separation and preconcentration employing knotted reactors (KRs) as a sorption medium for organometallic complexes associated to atomic spectrometry techniques is reviewed in this article, focusing the attention on the more frequently complexing agents used. In the last years, the KR has demonstrated to be an excellent alternative in the FI on-line preconcentration procedures; the on-line preconcentration and separation of different metallic species on the inner walls of the KR have been developed utilizing diverse organic and inorganic reagents. The choice of complexing reagents, the coupling of the FI preconcentration system to atomic spectrometry techniques, and the application of the methodologies developed to different samples are discussed.